The Uncanny Valley Theory and Application Towards Film and Animation - Siti Nor Fatihah, Ismail (Universiti Malaysia Sarawak (UNIMAS), 2021)
The 'Uncanny Valley' theory is an idea pioneered by Masahiro Mori in 1970 regarding the psychological effects of lifelike robotic (Mori, 1970). The definition of the uncanny valley implies that a humanoid target emerges in witnesses, and looks closely but not quite like human beings uncannily, or curiously similar. For decades, animation companies such as Pixar prefer to go for stylized animations instead of realistic animations to avoid negative audience reactions (Wolchover, 2011). This could be due to Masahiro's uncanny valley theory. Furthermore, even though there are multiple studies conducted with robots and still images of digital characters, the number of researches which focus on existence of uncanny valley in animation and film is still limited. Which means, either uncanny valley theory is important or not and is it the uncanny valley theory can give the effect to the animation itself? This unresolved problem is led to confusion among animators. This study aims to accomplish three goals: 1) identify the relationship between the uncanny valley with animation and film; 2) identify the effectiveness of uncanny valley theory in animation and film and; 3) To recommend the appropriate guideline for animators to overcome the uncanny valley effect in order to produce realistic animation and film. Other than that,this research will be conducted using Survey Research Method. Based on result of 123 participants, this research can be concluded that, when the character was very familiar to the audience, the more discomfort feeling when looking at the character after it builds with the CGI. The main objective of the study is to analyse the effect of the uncanny valley on the animation. This research is beneficial to the CGI industry (visual effects and post-productions) to create more details, realistic characters to attract audience attention, for bigger market sales. Keywords: Animation, humanoid reality, uncanny valley, virtual reality, visual analysis